2006
DOI: 10.1158/1078-0432.ccr-05-2619
|View full text |Cite
|
Sign up to set email alerts
|

Nonfucosylated Therapeutic IgG1 Antibody Can Evade the Inhibitory Effect of Serum Immunoglobulin G on Antibody-Dependent Cellular Cytotoxicity through its High Binding to FcγRIIIa

Abstract: Purpose: Recent studies have revealed that fucosylated therapeutic IgG1s need high concentrations to compensate for FcgRIIIa-competitive inhibition of antibody-dependent cellular cytotoxicity (ADCC) by endogenous human plasma IgG. Here, we investigated whether ADCC of nonfucosylated therapeutic IgG1 is also influenced by plasma IgG in the same way as fucosylated IgG1s. Experimental Design: Ex vivo ADCC upon CD20 + human B cells was induced by incubation of human whole blood with nonfucosylated and/or fucosylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(152 citation statements)
references
References 46 publications
3
149
0
Order By: Relevance
“…38 Defucosylation of Fc glycans could also circumvent the inhibitory effects both of plasma IgG on the binding of FcgRIIIa on NK cells and of fucosylated counterparts on the binding of the antigen on target cells. [39][40][41] Importantly, J6M0-mcMMAF and naked J6M0 significantly enhanced ADCC in vitro and anti-MM activity in vivo, when compared with its fucosylated normal Fc version. To our knowledge, J6M0-mcMMAF would be the first therapeutic ADC with defucosylated oligosaccharides entering clinical trials in MM.…”
Section: Discussionmentioning
confidence: 93%
“…38 Defucosylation of Fc glycans could also circumvent the inhibitory effects both of plasma IgG on the binding of FcgRIIIa on NK cells and of fucosylated counterparts on the binding of the antigen on target cells. [39][40][41] Importantly, J6M0-mcMMAF and naked J6M0 significantly enhanced ADCC in vitro and anti-MM activity in vivo, when compared with its fucosylated normal Fc version. To our knowledge, J6M0-mcMMAF would be the first therapeutic ADC with defucosylated oligosaccharides entering clinical trials in MM.…”
Section: Discussionmentioning
confidence: 93%
“…These include engineering the Fc region through amino acid mutations 12 and glycoengineering the Fc N -glycan to reduce core fucose. 13-15 It is now widely recognized that removal of the core fucose from Fc N -glycans represents the most effective approach to enhance ADCC activity 14 15 A high-throughput study of the IgG glycome of three isolated human populations showed that most of the human plasma IgG antibodies are core fucosylated with levels of afucosylated IgG ranging from 1.3% to 19.3%, underlying the difference in ADCC efficacy of naturally occurring antibodies to protect against diseases 16 .…”
Section: Introductionmentioning
confidence: 99%
“…12 For example, afucosylated anti-CD20 antibodies show higher B cell depletion than their fucosylated counterpart by reaching saturated ADCC levels at lower concentrations and through improved FcγRIIIa binding. 13 In addition, it has been reported that antibodies lacking the core fucose in The Fc portion of SMIP-016 GV has enhanced affinity for low and high affinity soluble FcγRIII. The single nucleotide polymorphisms (SNP) in FcγRIIIa resulting in either a valine (V) or phenylalanine (F) at position 158 results in low or high affinity receptors in humans, and this has been implicated to be indicative of response to rituximab immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 This has been described for CD20-directed antibody therapeutics where studies have shown enhanced NK cell ADCC function at lower antibody concentrations. 13,35,36 It provides the opportunity for using less therapeutic antibody, thereby diminishing production and ultimately treatment cost.…”
Section: Discussionmentioning
confidence: 99%